The last flight of the translator: translation and languages in Mia Couto's novel - Marini, Clarissa Prado (Programa de Pós-Graduação em Letras Vernáculas da Faculdade de Letras da UFRJ, 2016)
This study analyses the novel O último voo do flamingo (2005), by the Mozambican author Mia Couto, relating the characterization of the translator-narrator to the mystical milieu wherein he is inserted. Therefore, we identify how both translator and translation are characterized, articulated, and developed during the narrative. Results evince the degree of inter-dependence established between language and culture, endorsing a parallel between “speech” and “being”.